Analysis of leaves morphology similarity of several first generation tea clones - Sriyadi, Bambang (Research Institute for Tea and Cinchona, 2012)
As an effort to conserve tea clone accessions of first generation from genetic erosion, arrangement germplasm in one particular block/area to be easily monitored and managed, is needed. Ideally, tea germplasm collection should consist of a few clone accession number but high genetic variability. To select representative clones that will be conserved in new germplasm collection, leaves morphology similarity has been analysed by cluster analysis using average method. The results showed that by using leaves morphology parameter, from 50 tea clone accession of first generation coming from several tea plantations, it could be reduced into 25 clone accessions from seven clusters, which each has high similarity. The first cluster with 60% similarity could reduced accession from 15 to 6 clone. The second with 74,8% similarity from 25 to 13 clones. The third with 74,8% similarity, from 4 to 2 clones. The fourth with 61,3% similarity, and seventh with 82,1% similarity, both could reduce from 2 clones to 1 clone. To design a tea germplasm collection with 50 accessions of genetic variability, it could represented by 25 clones with low similarity, i.e PG 3, KP 1, Skm 18, Cin 69, Cin 67 dan Cin 58 as the first cluster representatives, Mel 101, PG 4, Pam 15, PG 5,Â PG 11, GP 2, BD 13, SA 49, Cin 66, Mal 16, Bks 6 and Sin 5 the second cluster representatives;Â Â Mel 108 and Cin 13 as the third cluster representatives; and Cin 15, Cip 37, GH 5, as well as GP 4 as the fourth, the fifth, and the sixth representatives, respectively.